2015
DOI: 10.3390/agriculture5041224
|View full text |Cite
|
Sign up to set email alerts
|

Grain Sorghum: A Conundrum for Chicken-Meat Production

Abstract: Abstract:The inclusion of grain sorghum in diets for broiler chickens is quite common; however, under Australian conditions, the utilisation of starch/energy by birds offered sorghum-based diets appears inadequate. Various factors inherent in sorghum, including kafirin, phenolic compounds and phytate, may limit energy utilisation. The recent quantification of kafirin, the dominant protein fraction in sorghum, has allowed its nutritional significance to be assessed. This is important as indirect evidence sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 87 publications
1
31
1
8
Order By: Relevance
“…Relative gizzard weights, or the "power of the gizzard", is pivotal to the practice of whole-grain feeding but even in the context of standard diets in which the entire grain component has been ground, the influence of the gizzard and its impact on gut function and reverse peristalsis appears to hold importance. Liu et al (2015b) suggested that the triad of kafirin, nontannin phenolic compounds and phytate in grain sorghum negatively influence the utilisation of starch/energy in broilers offered sorghum-based diets. The rationale for this suggestion has been considered in detail elsewhere (Khoddami et al, 2015;Liu et al, 2015b;Truong et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative gizzard weights, or the "power of the gizzard", is pivotal to the practice of whole-grain feeding but even in the context of standard diets in which the entire grain component has been ground, the influence of the gizzard and its impact on gut function and reverse peristalsis appears to hold importance. Liu et al (2015b) suggested that the triad of kafirin, nontannin phenolic compounds and phytate in grain sorghum negatively influence the utilisation of starch/energy in broilers offered sorghum-based diets. The rationale for this suggestion has been considered in detail elsewhere (Khoddami et al, 2015;Liu et al, 2015b;Truong et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2015b) suggested that the triad of kafirin, nontannin phenolic compounds and phytate in grain sorghum negatively influence the utilisation of starch/energy in broilers offered sorghum-based diets. The rationale for this suggestion has been considered in detail elsewhere (Khoddami et al, 2015;Liu et al, 2015b;Truong et al, 2015b). Tiger was clearly superior to Block I sorghum in the present study as significant advantages for feed conversion ratios, energy utilisation, starch and protein (N) digestibility were observed.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed considerations of the likely responsible underlying mechanisms may be found in two reviews (Selle et al 2013;Liu et al 2015). One recommendation arising out of this study is that white sorghum varieties with low-protein contents would be advantageous.…”
Section: Resultsmentioning
confidence: 99%
“…However, Liberty also contained lower concentrations of bound phenolic acids by 35.1% (229 vs mean of 353 mg/g) and total phenolic acids by 34.1% (303 vs mean of 460 mg/g) in comparison to the five red sorghum varieties (Table 7). In a comparison by Liu et al (2015), another sample of white sorghum (Liberty) contained lower concentrations of bound phenolic acids by 48.3% (282 vs 545 mg/g) and total phenolic acids by 41.3% (374 vs 637 mg/g) in comparison to a red sorghum (Buster). Thus, it appears that white sorghums may routinely contain lesser concentrations of both polyphenols and phenolic acids than red sorghums and, anecdotally, white sorghums as a feed grain for pigs and poultry are considered to be superior to red varieties under Australian conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For Liu et al (2015), the main factors restricting the use of protein sorghum concentrates on a large scale are: tannin content in the grain, type of cultivar (the white variety having lower levels of phytate and non-tanning phenolic compounds and higher CP and AMEn values compared to red sorghum), grain processing (with variations in gelatinization or complexation of nutrients, mainly starch and proteins) and the concentration of kaffirin and glutelin, the main protein fractions in sorghum. Selle et al (2017) stated that only kaffirin is related to increased protein in the endosperm of the sorghum grain, which may lead to low digestibility and complexation of carbohydrates and, mainly, amino acids.…”
Section: Feedstuffsmentioning
confidence: 99%